Aggressive interactions and consistency of dominance hierarchies of the native and nonnative cichlid fishes of the Balsas basin. Issue 1 (25th September 2021) - Franco, Marco; Arce, Elsah
Abstract: Dominance hierarchies are generally established based on the levels of aggressiveness that animals present. Frequently, animals fight to establish a dominance hierarchy and obtain a disputed resource. The Mexican mojarra Cichlasoma istlanum is a native species of the Balsas river basin and coexists there with four nonnative cichlids: tilapia Oreochromis sp., convict cichlid Amatitlania nigrofasciata, spotcheek cichlid Thorichthys maculipinnis, and green terror Andinoacara rivulatus . These five cichlid species compete for spaces for reproduction, feeding, and shelter and frequently engage in aggressive interactions to obtain these resources. We quantified dominance indices to evaluate the hierarchical structure of dominance among these five cichlids and the duration of aggressive behaviors of the Mexican mojarra during experimental contests between the native species and each of the four nonnative species. The Mexican mojarra was consistently dominant over the other four cichlid species, performing a larger number of aggressive behaviors and investing more time in attacking than the nonnative cichlids, which resulted in a higher hierarchical position. Our results show that the native fish, Mexican mojarra, established dominance over all four nonnative cichlid fish of the Balsas basin. Thus, the establishment of nonnative cichlid species in the Balsas basin is likely associated with factors other than behavioral dominance.